Teaching Writing Skill through Collaborative Writing Technique: From Theory to Practice - Supiani (JEELS (Journal of English Education and Linguistics Studies), 2017)
Based on the school based curriculum states that the teaching of writing skill is aimed at enabling students to master the functional and monologue texts in the form of genres. However, previous studies revealed that Indonesian students still have problems in learning it because writing itself involves aspects of grammatical form, choice of words, generating and organizing the ideas into coherent and logically ordered. Those have become a hard challenge for many students in Indonesia. To overcome this, collaborative writing technique is one of writing techniques to help students learn and develop their writing. This article discusses it from both theoretical perspective and pedagogical procedures for teaching writing of collaborative writing technique.